The Use of Artificial Intelligence Technology in Learning for Children with Special Needs - Harimurti, Eka Rista (Civiliza Publishing, Indonesia., 2025)
In the era of the industrial revolution 4.0 and rapid development towards the era of society 5.0, the use of digital technology has become an important aspect in various fields of life, including in the world of education. This study aims to analyze the Utilization of Artificial Intelligence Technology in Learning for Children with Special Needs. The research method used is a literature review. The results of the study show that the use of Artificial Intelligence (AI) technology in learning for children with special needs has a significant positive impact, especially in creating a more personal, adaptive, and interactive learning approach according to the needs of each student. AI is able to help teachers analyze students' abilities and learning progress in real-time, as well as provide learning materials and methods that are tailored to each child's learning style. In addition, this technology can also increase students' motivation and independence in learning through the use of AI-based applications or devices that are user-friendly and easy to access. Thus, the application of AI is an innovative solution in creating an inclusive and effective learning environment for children with special needs.